Brust-CT als alternative Bildgebung im Brustkrebs-Screening in Deutschland: das ProHTA-Simulationskonzept - Meier, Florian; Ruile, Georg; Djanatliev, Anatoli; Kriza, Christine; Leb, Ines; Schöffski, Oliver; Kalender, Willi Alfred; Kolominsky-Rabas, Peter (Tagungsband der 7. Jahrestagung der Deutschen Gesellschaft für Gesundheitsökonomie, 2015)
UnivIS-Import:2016-06-01:Pub.2015.tech.IMMD.IMMD7.brustc

Screening for breast cancer with Breast-CT in a ProHTA simulation - Ruile, Georg; Djanatliev, Anatoli; Kriza, Christine; Meier, Florian; Leb, Ines; Kalender, Willi Alfred; Kolominsky-Rabas, Peter (Journal of Comparative Effectiveness Research, 2015)
Aims: The potential of dedicated Breast-CT is evaluated by simulating its impact onto the performance of the German breast cancer screening program. Attendance rates, cancer detection and economic implications are quantified. Methods: Based on a prospective health technology assessment approach, we simulated screening in different scenarios. Results: In the simulation, attendance rates increase from 54 to up to 72% due to reduced pain. Breast cancers will be detected earlier while nodal positives and distant recurrences decrease. Assuming no additional cost, cost savings of up to 55 million in one screening period are computed. Conclusion: The simulation indicates that earlier cancer detection, fewer unnecessary biopsies and less pain are potential benefits of Breast-CT resulting in cost savings and higher attendance.
UnivIS-Import:2016-06-01:Pub.2015.tech.IMMD.IMMD7.screen
Keywords: breast cancer; computed tomography; health economics; health technology assessment; mammography screening; simulation